Ocean of sound: ambient music, mondes imaginaires et voix de l'éther - Toop, David; Réveillon, Arnaud (France Kargo & Eclat, 2004)
Ocean of Sound begins in 1889 at the Paris Exposition when Debussy first heard Javanese music performed. A culture absorbed in perfume, light and ambient sound developed in response to the intangibility of 20th century communications. David Toop traces the evolution of this culture, through Erik Satie to the Velvet Undergound; Miles Davis to Jimi Hendrix.David Toop, who lives in London, is a writer, musician and recording artist. His other books are Rap Attack 3 and Exotica.